DINÁMICA DEL AGUA DEL SUELO EN DEHESA BAJO DIFERENTES CUBIERTAS VEGETALES. RESULTADOS PRELIMINARES. - Lozano Parra, F J; Schnabel, S; Ceballos Barbancho, A (Estudios en la Zona no Saturada del Suelo, 2008)
Dehesa ecosystems, characterized by a disperse tree cover of the genus Quercus, constitute a resource of great importance in large parts of SW Iberian Peninsula. Generally these areas are conditioned by their environmental limits such as shallow soils, seasonal and intraannual rainfall variability, which determine the availability of water for plants. The main objective of the present work is the study of soil water dynamics in dehesas, explaining the effect of different vegetation covers and soil characteristics. Soil moisture is determined in 15 stations, distributed in three farms in Extremadura, each of them composed of sensors located at various depths which register soil moisture continuously with a time resolution of 30 minutes. The stations are distributed in open areas (pasture), below the canopy of the shrub Retama sphaerocarpa and below the canopy of Quercus rotundifolia. First results indicate complex soil water dynamics with contrasting situations at sites with the same vegetation cover, and showing that various situations may be produced in the same station during a hydrological year. Furthermore, the largest variations are observed in the upper soil layer, being soil moisture variations lowest at greater depth, independently of the vegetation cover.
Keywords: bajo copa; Dehesa; humedad del suelo; pastizal; Quercus rotundifolia (voyant); retama sphaerocarpa

DINÁMICA DEL AGUA DEL SUELO EN DEHESA BAJO DIFERENTES CUBIERTAS VEGETALES. RESULTADOS PRELIMINARES. - Lozano Parra, F. J.; Schnabel, S.; Ceballos Barbancho, A. (Estudios en la Zona no Saturada del Suelo, 2008)
Dehesa ecosystems, characterized by a disperse tree cover of the genus Quercus, constitute a resource of great importance in large parts of SW Iberian Peninsula. Generally these areas are conditioned by their environmental limits such as shallow soils, seasonal and intraannual rainfall variability, which determine the availability of water for plants. The main objective of the present work is the study of soil water dynamics in dehesas, explaining the effect of different vegetation covers and soil characteristics. Soil moisture is determined in 15 stations, distributed in three farms in Extremadura, each of them composed of sensors located at various depths which register soil moisture continuously with a time resolution of 30 minutes. The stations are distributed in open areas (pasture), below the canopy of the shrub Retama sphaerocarpa and below the canopy of Quercus rotundifolia. First results indicate complex soil water dynamics with contrasting situations at sites with the same vegetation cover, and showing that various situations may be produced in the same station during a hydrological year. Furthermore, the largest variations are observed in the upper soil layer, being soil moisture variations lowest at greater depth, independently of the vegetation cover.
Keywords: bajo copa; Dehesa; humedad del suelo; pastizal; Quercus rotundifolia (voyant); retama sphaerocarpa